(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2020)
Additive manufacturing (AM) represents an excellent tool to accelerate the product development process. Used as modern manufacturing technology it still has to compete with traditional technologies like e.g. injection molding. Having both technologies in house available, cirp GmbH faces decision making for the adequate tool within that context at first hand. A good example is the ramped up development of 2 corona devices namely a reusable respirator mask and an aerosol protection face-shield. This work assesses the cost and benefits and the subsequent production decisions using the example of those 2 devices.